Analisis Sistem Fonetik Penggunaan Bahasa Madura pada Masyarakat Klenang Lor Probolinggo - Nuning Indagwiya; Weni Febriyanti; Novi Afriliya; Hasan Suaedi (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
This research aims to analyze the phonetic system in the use of Madurese in the Klenang Lor community, Probolinggo. Madurese is one of the regional languages ​​in Indonesia which has phonetic and phonological characteristics, making it interesting to study in the sociolinguistic context of local communities. The research method used is descriptive qualitative with data collection through interviews, observation and documentation. The results of the analysis show that the Klenang Lor people tend to use Madurese with the influence of local dialects which influence the pronunciation of vowels, consonants and intonation. Certain phonemes such as /ʈ/, /ɖ/, and /ʔ/ have an important role in distinguishing word meanings. Apart from that, there are phonetic adaptations that occur due to interactions with Javanese and Indonesian as the dominant languages ​​in the area. This study also found a shift in the use of Madurese among the younger generation who more often use Indonesian in daily communication. This research contributes to the preservation of regional languages ​​and becomes a reference for more in-depth linguistic studies. It is hoped that these findings will provide insight into how Madurese language phonetics are maintained and adapted in a multilingual society.